ACTIVITY OF OIL REFINING ENTERPRISES IMPROVEMENT OF MANAGEMENT SYSTEM - Uzakov Barkhayotjon Muhammadievich (European Science Publishing, 2024)
To establish effective inter-country electronic systems and accounting of production costs based on internal standards in order to make rational management decisions in determining the cost of products in oil refining industries in the economy of Uzbekistan. Improving the management system of oil refining enterprises, searching for the most appropriate product cost determination schemes adapted to increase the competitiveness of economic entities, econometric modeling and forecasting of factors affecting production costs, and improving the quality and improvement of raw materials handling services have become urgent issues.
Keywords: Oil refining, management system improvement, modeling.